(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Today, distance learning has entered the educational system as a convenient and unique type of education. Distance education is a form of obtaining information in which, in addition to full-time and part-time education, traditional and innovative methods, tools and forms of education based on computer and telecommunication technologies are widely used. In the distance education tool, a controlled educational process focused on one goal is organized using special opportunities, telephone, electronic communication and other educational tools based on an individual schedule in a place convenient for the student. This article focuses on the specific features and advantages of distance education.